HUBUNGAN ACTIVITY DAILY LIVINGROOM DENGAN STABILITAS TEKANAN DARAH PADA PASIEN STROKE ISKEMIK (Studi Di Irna B Rsud Syarifah Ambami Rato Ebhu Bangkalan) - Faisal Amir (NHM PRESS, 2019)
Ischemic stroke is a syndrome that has thecharacteristic of a sudden, non-occlusive attackcaused by non traumatic brain circulatorydisorder. From the preliminary study resultsobtained data that from 10 respondents obtainedis still many patients with ischemic stroke withunstable blood pressure. The purpose of thisstudy was to analyze the relationship of physicalactivity with blood pressure in stroke patients inIrna B Syamrabu Bangkalan Hospital. In this study, the type of research used iscross sectional analytic research. The populationof 32 patients in Irna B Syarifah hospital ambamirato ebu bangkalan with sample of 30 patientsthrough Simple random sampling technique.Independent variable is physical activity anddependent variable Blood pressure. Datacollection for physical activity using questionnairesheet, for blood pressure using observationsheet. Statistical test using Somer's D. Based on the result of cross-tabulation ofphysical activity relationship with blood pressurein ischemic stroke patients in IRNA B SyarifahAmbami Rato Ebhu Bangkalan Hospital showedthat from 14 ischemic stroke patients with lessphysical activity, almost all of them had unstableblood pressure, 13 respondents Based on the results of statistical tests ofSomer's D, the results obtained ρ value <α (0.05)so that H0 rejected and H1 is accepted whichmeans there is a relationship between physicalactivity with blood pressure in patients ischemicstroke. The results of this study can be used as areference or comparison for further research andas a source of patient iformasi to be able toregulate their physical activity so that bloodpressure can be stable